PERAN BIAS KOGNITIF DALAM MENJELASKAN EFEKTIVITAS MANAJEMEN KEUANGAN PELAKU UMKM KULINER PASAR RAMADHAN DI DESA TAMBAKREJO - Beni Sucipto; Saiful Aminudin Al Kusuma Putra (STIE PGRI Dewantara Jombang, 2024)
This study aims to analyze the role of cognitive bias in explaining the effectiveness of financial management among MSME actors in Tambakrejo Village, Jombang. A quantitative approach with an explanatory research design was employed using a survey method. Data were collected through a 5-point Likert-scale questionnaire measuring cognitive biases (e.g., overconfidence, anchoring, confirmation bias, availability bias, and loss aversion) and financial management effectiveness (financial planning, recordkeeping, budgeting, financial control, and financial evaluation). The sample consisted of 60 culinary MSME operators participating in the Ramadan Market in Tambakrejo, Jombang, selected using total sampling based on predetermined criteria. Data analysis was conducted using SPSS version 24, including descriptive statistics, instrument quality testing (validity and reliability/Cronbach’s alpha), classical assumption tests, and hypothesis testing using linear regression (t-test and the coefficient of determination, ) at a significance level of 0.05. The findings are expected to provide empirical evidence on how cognitive biases influence financial decision-making and, in turn, affect the effectiveness of financial management among culinary MSMEs, thereby informing more targeted financial literacy and business mentoring programs for MSME actors in the study area.